THE INFLUENCE OF ONLINE CUSTOMER REVIEWS, ONLINE CUSTOMER RATINGS, AND CELEBRITY ENDORSERS ON E-COMMERCE SHOPEE PURCHASING DECISIONS (Study on Generation Z in Tahunan District) - Duhita Sari, Cindy Ratna; Arifin, Samsul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to determine the influence of online customer reviews, online customer ratings and celebrity endorsers on Shopee e-commerce purchasing decisions among generation Z in Tahunan sub-district. The population is generation Z in Tahunan sub-district. The total sample was 100 respondents from Generation Z, Tahunan sub-district, which was calculated using the Slovin formula. Purposive sampling is the technique used for collecting this data. Data collection through questionnaires was analyzed using SmartPLS-4. The research results show that the existence of online customer review (X1) has a positive, significant influence on purchasing decisions. Online customer rating (X2) has a positive, significant influence on purchasing decisions. Celebrity endorser (X3) has a positive, significant influence on purchasing decisions. It can be concluded that online customer reviews, online customer ratings, and celebrity endorsers together have a positive, significant influence on purchasing decisions.